Penerapan Metode Pembelajaran Students Fasilitator and Explaining Menggunakan Media Vlog Pada Pembelajaran IPS di Sekolah Menengah Atas Negeri 1 Bojong Gede Kab. Bogor - Sahat T. Simorangkir; Nusirwan Nusirwan; Eliza Meliana; Sumiyanti Sumiyanti; Meiyanti Fitriyani; Rendi Agashi; Farhan Atha Syarif (Jurnal Pengabdian Masyarakat, 2025)
The title of this activity is "Implementation of the Students Facilitator and Explaining Learning Method Using Vlog Media in Social Studies Learning at State Senior High School 1 Bojong Gede, Bogor Regency." This activity aims to improve teacher teaching skills and student activeness in Social Studies (IPS) learning through the application of the Students Facilitator and Explaining method combined with digital media in the form of vlogs. This method encourages students to actively explain the material to their classmates with teacher guidance, while vlog media is used as a means to document and convey their understanding creatively. In addition to improving material understanding, this approach is also expected to develop students' communication, collaboration, and digital literacy skills. The activity will be implemented through training for Social Studies teachers at State Senior High School 1 Bojong Gede, mentoring in implementing the method in the classroom, and evaluating the results of the implementation. It is hoped that this activity can be an innovative alternative in the learning process that is more fun, interactive, and relevant to technological developments.